2009
DOI: 10.1007/s12403-009-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

Initial Test of a Subsurface Constructed Wetland with Green Sorption Media for Nutrient Removal in On-site Wastewater Treatment Systems

Abstract: Conventional on-site wastewater treatment systems are no longer able to fully meet the needs of coping with the impacts of the variegated pollutants with which they are confronted. Without proper nitrification and denitrification, this implies a large fraction of nutrient loads such as nitrogen and phosphorus will flow into groundwater aquifers adversely affecting the water quality and public health. Constructed wetland, a cost-effective small-scale wastewater treatment system with low energy, maintenance requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…However, a recent study conducted by Harden et al (2010) reported through monitoring thirty-five performance based septic systems in Wakulla County that such performance based septic systems are only capable of producing a 50e60% reduction of total nitrogen from raw sewage inputs of 72.8 AE 39.2 mg-N/L. It should be noted that this is still superior to the total nitrogen reduction of conventional septic tanks which is about 10e25% (Lowe et al, 2009;Xuan et al, 2009). This study also reported that monthly average effluent concentrations from these septic systems can be in the range of 29 AE 19 mg-N/L, which are higher than the targeted treatment standard of 10 mg-N/ L. Considering the fact that active systems discharge 1.0 Â 10 11 L/yr of treated effluent, estimated total nitrogen released from these septic systems may range from 1.0 Â 10 10 to 4.9 Â 10 10 g-N/yr without accounting for the environmental attenuation.…”
Section: Septic Systemsmentioning
confidence: 99%
“…However, a recent study conducted by Harden et al (2010) reported through monitoring thirty-five performance based septic systems in Wakulla County that such performance based septic systems are only capable of producing a 50e60% reduction of total nitrogen from raw sewage inputs of 72.8 AE 39.2 mg-N/L. It should be noted that this is still superior to the total nitrogen reduction of conventional septic tanks which is about 10e25% (Lowe et al, 2009;Xuan et al, 2009). This study also reported that monthly average effluent concentrations from these septic systems can be in the range of 29 AE 19 mg-N/L, which are higher than the targeted treatment standard of 10 mg-N/ L. Considering the fact that active systems discharge 1.0 Â 10 11 L/yr of treated effluent, estimated total nitrogen released from these septic systems may range from 1.0 Â 10 10 to 4.9 Â 10 10 g-N/yr without accounting for the environmental attenuation.…”
Section: Septic Systemsmentioning
confidence: 99%
“…This is of importance because hydraulic conductivity affects the P sorption. In percolating on-site system, the sorption media that have been studied include, but are not limited to, sawdust, peat, compost, zeolite, wheat straw, newspaper, sand, limestone, expanded clay, wood chips, wood fibers, mulch, glass, ash, pumice, bentonite, tire crumbs, expanded shale, oyster shells, and soy meal hulls (Hossain et al 2010a, b;Xuan et al 2009). This approach was adjudged to have ''green'' implications because of the inclusion of recycled material as part of the material Appl Water Sci (2017) 7:3391-3406 3399 mixture, promoting treatment efficiency and cost effectiveness (Hossain et al 2010a).…”
Section: Nutrients (Ie P and N)mentioning
confidence: 99%
“…It is based on second-order reaction kinetics and the assumption of Langmuir isotherm to give an analytical solution that allows for a nonlinear equilibrium relationship (Mustafa and Ebrahim, 2010). Based on previous literature of these materials used as sorption media for nutrient removal Xuan et al, 2009a), it was hypothesized that media would adsorb orthophosphate at a high efficiency which should decrease with less exposure or HRT with the orthophosphate solution.…”
Section: Column Testsmentioning
confidence: 99%
“…A wide variety of sorption media have been effective at reducing nutrient levels for stormwater, including recycled material mixtures ; mineral-based mixtures such as marble chips (Sengupta and Ergas, 2006) and oyster shells (Namasivayam et al, 2005), and organic materials such as leaf mulch (Ray et al, 2006), wood chips (Seelsaen et al, 2006) and alfalfa (Kim et al, 2000). Such media were selected for testing, which was composed of clay, sand, organic materials, or engineered compounds to remove more soluble reactive phosphorus (SRP) and total phosphorus (TP) Xuan et al, 2009a;Chang et al, 2010). For instance, a new media mixture composed of cement sand, tire crumb, fine expanded clay, and limestone, was selected on the basis of its removal efficiencies, surface area, particle size, cost, and availability in Florida (Xuan et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation